2018
DOI: 10.1093/jxb/ery145
|View full text |Cite
|
Sign up to set email alerts
|

Fruit-localized phytochromes regulate plastid biogenesis, starch synthesis, and carotenoid metabolism in tomato

Abstract: Fruit-localized phytochromes and their downstream signaling cascades not only modulate chloroplast biogenesis in immature tomato fruits but also regulate sugar and carotenoid accumulation, two essential features of tomato fruit quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
69
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(79 citation statements)
references
References 78 publications
5
69
2
3
Order By: Relevance
“…On the contrary, silencing of the negative regulators of light signalling SlDDB1 and SlCUL4 led to a significant increment in the number of plastids that resulted in enhanced carotenoid and flavonoid accumulation during ripening (Wang et al, ). In particular, a positive role of PHY‐dependent light response cascade in fruit carotenogenesis has been demonstrated (Alba, Cordonnier‐Pratt, & Pratt, ; Bianchetti et al, ; Llorente et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, silencing of the negative regulators of light signalling SlDDB1 and SlCUL4 led to a significant increment in the number of plastids that resulted in enhanced carotenoid and flavonoid accumulation during ripening (Wang et al, ). In particular, a positive role of PHY‐dependent light response cascade in fruit carotenogenesis has been demonstrated (Alba, Cordonnier‐Pratt, & Pratt, ; Bianchetti et al, ; Llorente et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, silencing of the negative regulators of light signalling SlDDB1 and SlCUL4 led to a significant increment in the number of plastids that resulted in enhanced carotenoid and flavonoid accumulation during ripening (Wang et al, 2008). In particular, a positive role of PHYdependent light response cascade in fruit carotenogenesis has been demonstrated (Alba, Cordonnier-Pratt, & Pratt, 2000;Bianchetti et al, 2018;Llorente et al, 2016). Tocopherol biosynthesis is highly dependent on Chl degradationderived phytol (Almeida et al, 2016), and consequently, the rising of tocopherol content from MG to the ripe stage of fruit development correlates with the amount of Chl right before the onset of ripening.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tomato, five PHY-encoding genes, namely PHYA, PHYB1, PHYB2, PHYE and PHYF, have been identified (Alba et al, 2000a). PHYB2 is the most expressed in tomato fruits (Bianchetti et al, 2017;Hauser et al, 1997;Pratt et al, 1995) and a major regulator of fruit chloroplast maturation and carotenoid accumulation (Bianchetti et al, 2018;Gupta et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The Solanum lycopersicum genome harbours ve PHYencoding genes: PHYA, PHYB1, PHYB2, PHYE and PHYF 22 . Previous studies have shown that PHYA, PHYB1 and PHYB2 are major regulators of fruit chloroplast maturation and nutraceutical compound accumulation [23][24][25][26] . In this work, the genome-wide transcriptome and methylome were comprehensively analysed in fruits from phyA and phyB1B2 null mutants, revealing that PHY-dependent DNA demethylation is a crucial stimulus for triggering ripening-associated gene expression.…”
Section: Introductionmentioning
confidence: 99%